Depression in women with polycystic ovary syndrome: the role of body mass index and infertility on it - Seyedeh Marziyeh Rahebi; Atefeh Ghanbari; Parvaneh Reza Soltani; Hajar Sharami; Shirin Aramesh; Naeima Khodadadi; Maryam Moridi (Tehran University of Medical Sciences, 2016)
Background & Aim: Polycystic ovary syndrome (PCOS) is related to symptoms that lead to psychological disorder. This study was aimed to compare the depression score between women with and without (controls) PCOS. Methods & Materials: This comparative study was performed on 174 women from March to October 2014 in Rasht, Iran. Cases were 58 women who met currently recognized definitions of PCOS while the controls were 116 healthy women and groups were matched on socio-demographics and obstetrics characteristics. The universal assessment of ultrasonographic parameters, hormonal profiles, and clinical histories was used to diagnose PCOS. Depression was assessed by using the Beck Depression Inventory II. We estimated the mean scores of depression in both groups and investigated the comparison between them. Results: The mean depression score in PCOS women (30.31 ± 8.39) was significantly more than controls (23.36 ± 12.57) (P < 0.0001), indicating greater psychological distress. Multivariate analysis revealed the age of participants as a significant predictor of depression. Conclusion: The high prevalence of depression in PCOS indicates that initial assessment of all women with PCOS should also consist the evaluation of mental health disorders. The physicians should pay more attention to history of their patients, especially in view of the factors affecting psychological well-being.